The effect of teaching with the mathematics activity based on purdue model on critical thinking skills and mathematics problem solving attitudes of gifted and non-gifted students - ÖZDEMİR, AHMET ŞÜKRÜ (ELSEVIER SCIENCE BV, 2012)
The purpose of this study is to design an example activity based on Purdue Model (PM) about The Arithmetic of Conscious Consumption (ACC) unit for 7 th grade gifted students (GS) and non-gifted students (NGS) (25 G, 22 NG) in our country and to investigate the effects of this activity on critical thinking skills (CTS) and mathematical problem solving attitudes (MPSA) of these students. Eventually, it is concluded that the activity designed based on PM is more effective than the activities included in the National Education curriculum (NEC) on CTS and MPSA of G and NG students. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylut
Keywords: Giftedness; Purdue model; critical thinking skills; mathematics problem solving attitude; ENRICHMENT